Implementation of Performance Measurement Using the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) and SWOT Analysis to Achieve Competitive Excellence: Implementasi Pengukuran Kinerja Model Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) dan Analisa SWOT Untuk Kinerja Unggul Bersaing - Wahyu Ivan Syahputra; Ni Luh Putu Hariastuti (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2026)
The rapid technological development in this era has revolutionized the business world, providing significant impact on both service and product sectors. In service provision, service quality is influenced by various factors, particularly company performance. This decline in performance quality is not caused by a single aspect alone, but rather by the complexity of interrelated internal factors within a company. To analyze the company performance at CV JKK, an approach using the Malcolm Baldrige Criteria for Performance Excellence method with seven criteria and SWOT analysis is employed as strategic planning for proposed company strategies. From the measurement results using the MBCfPE method, a total Malcolm Baldrige score of 808 was obtained with a percentage of 80.8% from the total overall score of 1,000. This value indicates that the company is at the Excellent level and falls into the Benchmark Leader category with a point range between (776 – 875). The SWOT analysis results show that the company is in an advantageous strategic position in the first quadrant (S-O Strategy). This position indicates that the company has solid internal strengths and faces promising external opportunities. Based on this condition, the company is recommended to implement an aggressive strategy by maximizing all internal assets and advantages to gain optimal benefits from the opportunities available in the external environment. This approach is expected to accelerate the achievement of sustainable business growth targets.